The role of the European Union in Implementing the UN Sustainable Development Agenda - Pánovics, Attila (POLARITIES, 2023)
2023 is an important date in the implementation of the UN’s objectives for the period up to 2030. The experiences of the years since 2015 make it increasingly urgent for the international community to confront the very limited results within the framework of the mid-term evaluation of the Agenda 2030 program. This paper reviews the history of the program, the current situation of its implementation, and examines separately the role of the European Union, which is increasing its participation in the management of global challenges in an international comparison, serving as a model for other regions of the world.